Risks of conservative gynecological surgery: Discussion of the Round Table - Rozada, Héctor; Biderman de Rozada, Iris (Cirugía del Uruguay, 1973)
The different complications of conservative gynecological surgery are evaluated. Said compllcations are related to disease_ and type oí surgery performed. They can be divided into immediate and mediate. Immediate postsurgical complications comprise infections, hemorrhages, phlebitis and intestinal problems. Their incidence and · prophylaxis are discussed. Mediate complications are those connected with functional future of the organ or. with appearence therein of pathology. Frequency and actual importance of said accidents is considered, especially with respect to their weight in deciding on conservative gynecological surgery.